A MULTIMODAL ANALYSIS OF THE PHILIPPINE BROADSHEET FRONTPAGE COVERS IN THE COVID-19 PANDEMIC SITUATION - Tora Gorobat, Chaterine (Universitas Muhammadiyah Lampung, 2023)
The threat of Covid-19 continues to plague the whole world including the Philippines.Hence, the need of the people to access news information from all media sources such as the broadsheets has never been as primordial as before. Broadsheets are considered aesthetic genrewhich combined words and pictures to convey news realities. Hence, this study analyzed howlanguage and visual elements delivered meanings about the COVID-19 situation in the countryas portrayed in the front covers of selected broadsheets using the Gibbons, Koszary, and Tandi’s Non-Literary Reading approach. The study showed that Manila Bulletin and Philippine Daily Inquirer front covers disseminate negative emotions, warnings, and fear thaturge the Filipino to be vigilant. However, The Manila Times broadsheet disseminates positive emotion, hope, and encouragement to the Filipinos to get vaccinated. This implies that visualfeatures in multimodal texts are related to the message of the whole, and that visual meaning is becoming the most significant in this multimodal world. Therefore, the researcher recommends this innovative technique for analyzing multimodal text to learn how to interpretthe text, visual elements, and understand the message just by looking at the visual surface.